2007
DOI: 10.1128/jb.00375-07
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids pMOL28 and pMOL30 of Cupriavidus metallidurans Are Specialized in the Maximal Viable Response to Heavy Metals

Abstract: We fully annotated two large plasmids, pMOL28 (164 open reading frames [ORFs]; 171,459 bp) and pMOL30 (247 ORFs; 233,720 bp), in the genome of Cupriavidus metallidurans CH34. pMOL28 contains a backbone of maintenance and transfer genes resembling those found in plasmid pSym of C. taiwanensis and plasmid pHG1 of C. eutrophus, suggesting that they belong to a new class of plasmids. Genes involved in resistance to the heavy metals Co(II), Cr(VI), Hg(II), and Ni(II) are concentrated in a 34-kb region on pMOL28, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
235
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(243 citation statements)
references
References 43 publications
5
235
0
3
Order By: Relevance
“…Another study showed that multiple-metal responses by genes belonging to the cop, cnr, mer, and pbr loci occurred after challenging C. metallidurans CH34 with Cd 2ϩ , Pb 2ϩ , Zn 2ϩ , and Cu 2ϩ (28). This suggests that C. metallidurans uses several strategies to reduce the intracellular concentration of toxic metal ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that multiple-metal responses by genes belonging to the cop, cnr, mer, and pbr loci occurred after challenging C. metallidurans CH34 with Cd 2ϩ , Pb 2ϩ , Zn 2ϩ , and Cu 2ϩ (28). This suggests that C. metallidurans uses several strategies to reduce the intracellular concentration of toxic metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…The DNAbinding transcriptional activator CupR (Rmet3525), an ortholog of CueR in Escherichia coli and GolS in S. enterica, the Cutransporting P-type ATPase CopA, as well as CopI, and the putative electron transferring cytochrome C-type copJ were strongly upregulated, suggesting their involvement in efflux and reduction of Au(III/I) to Au(0) (12,26,27). Experiments with C. metallidurans had demonstrated the induction of cupR with Au(I) (28). This suggests that the cup/cop system is a general metal response system that is readily inducible at low levels of metal stress, rather than a Cu-specific resistance system.…”
Section: Effect Of and Response To Au(iii)-complexes On C Metallidurmentioning
confidence: 99%
“…ZraP is a metal-binding protein that is induced by a two-component system that responds to zinc or lead (33,42), while CnrX is thought to act as a metal sensor that binds cobalt, nickel, and potentially copper in an extracytoplasmic function (ECF)-sigma factor signaling pathway (18,19,34,38,61). Interestingly, copper ions have been implicated as an inducer of the Cpx pathway (26,(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%
“…Cupriavidus metallidurans CH34 [28,29], Escherichia coli JM109 (pTP6) [26] and Cupriavidus necator JMP134 (pJP4) [30] were grown in Luria Bertani (LB) medium (contained per l: 10 g tryptone, 5 g yeast extract and 10 g NaCl) [31] [28]. Succinate (0.3%) was used as sole carbon source.…”
Section: Bacteria Plasmids and Culture Conditionsmentioning
confidence: 99%